Ragam Kerusakan atas Perbuatan Manusia di Muka Bumi dalam Penafsiran Ibn Katsir - Nia Ariyani (Al-Fanar: Jurnal Ilmu Al-Qur’an dan Tafsir, 2020)
This research examines the various kinds of damage caused by human actions on earth. It should be explored. This is because the word damage or in Arabic is called fasād has different and varied implications. These impacts can be in the form of material damage impacts and non-material damage impacts. However, the object of interest is in humans. Humans on this earth are basically people who have a religion. This raises a question, why do people who have religion participate in the destruction? Religious people should actually take care and even repair them. This research uses descriptive-analytical. This is aimed at obtaining a comprehensive understanding of the various types of damage caused by human actions. The method used to collect the main data, namely verses related to damage with the keyword term fasād and its derivations using the book al-Mufrād fī Gharīb Al-Qur'ān. The data will then be analyzed using Ibn Katsir's interpretation which focuses on the bi al-Matsur method.